Direct thermal annealing synthesis of FeO nanodots anchored on N-doped carbon nanosheet for long-term electrocatalytic oxygen reduction. (1st December 2021) - Wu, Meiying; Wu, Xiuzhen; Wang, Zeming; Hu, Bingjie; Guo, Huazhang; Zhang, Baohua; Wang, Liang
Abstract: It is highly desired to exploit non-noble metal oxide catalysts for superseding the Pt-based material and achieving long-term oxygen reduction reaction (ORR). Herein, a FeO-based ORR catalyst is firstly designed and synthesized by a one-pot pyrolysis strategy using FeCl3 and N-doped carbon nanosheets (NCNSs) as precursors. The NCNSs substrate play the important role to control the size of gained FeO at nanodot level (near 2.5 nm). The supersmall FeO nanodots, uniformly dispersion on the NCNSs, which enhance the touching areas with the NCNSs substrate and expose richen active sites. The introduction of FeO nanodots improve the graphitization degree of the composite and form Fe-N bonds in FeO/NCNSs, then exhibiting excellent electrocatalytic performance and long-term stability. The catalyst displays a high half-wave potential and small Tafel slope of 0.94 V and 56.9 mV dec −1 in the 4 electron ORR process, respectively. Meanwhile, it demonstrates superior tolerance to methanol. Noting, after 150 h i t-test, the current density only drops by 10.7%, even better than the durability performance of many catalysts after 10 h. The theoretical calculations further reveal that the OH* adsorption on the surface of FeO/NCNSs in real reaction environment is beneficial for embedding the FeO NDs in N6 hollow of NCNSs, which sustains the highly efficient ORR activity under the long-term running conditions. Our work opens a new era for the novel FeO-based ORR catalysts and provides a design reference for the long-term ORR electrode. Graphical abstract: Image, graphical abstract